OP74 Maternal smoking during pregnancy and risk of type 1 diabetes: whole-of-population study. (3rd September 2019) - Begum, M; Pilkington, RM; Chittleborough, CR; Lynch, JW; Penno, M; Smithers, LG
Abstract : Background: Evidence about maternal smoking during pregnancy and type 1 diabetes (T1D) risk is inconsistent. Most studies have small numbers of children exposed to prenatal smoking, and some were unable to look at timing of exposure to smoking, or were at risk of bias due to unmeasured confounding. Therefore, the objectives of this study were: 1) to estimate the association between prenatal smoking and T1D risk, looking at the timing of exposure to smoking (throughout pregnancy, first-half, or second-half of pregnancy), with adjustment for a range of confounding factors defined a priori; 2) to perform a negative-control outcome analysis to detect bias due to unmeasured confounding; and 3) to combine estimates from population-based and case-control studies in meta- analyses. Methods: This whole-of-population study of children born from 1999–2013 (n=286, 058, aged <15 years) used de-identified linked administrative datasets from the South Australian Early Childhood Data Project. T1D was diagnosed for 557 children during hospitalization (ICD-10-AM codes, E10, E101-E109) from 2001–2014. Maternal smoking data was sourced from the South Australian Perinatal Statistics Collection, where information at birth is collected by midwives/neonatal nurses using a validated tool. Hospitalization for any injury occurring at school was used as a negative-control outcome. Adjusted Cox proportional hazard ratios (HR) were calculated in the main analysis and the negative-control outcome. Random-effects meta-analysis was used to summarize effects of prenatal smoking on childhood T1D. Results: Compared with non-smokers, smoking throughout pregnancy was associated with 23% lower childhood T1D risk (HR 0.77; 95% CI 0.60–1.00), with similar effects for smoking in first-half (HR 0.78; 95% CI 0.60–1.01) and second-half (HR 0.75; 95% CI 0.57–0.98) of pregnancy. The negative-control outcome analysis (HR 0.95; 95% CI 0.86–1.05) suggested the effect of prenatal smoking on T1D was not due to unmeasured confounding. These results were consistent with meta-analytic estimates of prenatal smoking and childhood T1D risk from population-based (HR 0.70; 95% CI 0.60–0.81) and case-control studies (OR 0.71; 95% CI 0.55–0.86). Conclusion: Maternal smoking in pregnancy was associated with lower risk of childhood T1D. The negative-control outcome analysis suggests this effect is unlikely to be due to unmeasured confounding. Our meta-analytic estimates also showed lower risk of T1D for children exposed to maternal smoking during pregnancy. Smoking causes irreversible harm to the fetus, however understanding the mechanism of protective effects (e.g. nicotine exposure, gene expression) might lead to new insights about T1D.